Centrifugal self-layering type neutron absorbing material and preparation method and application thereof
Patent Information
- Application Number
- CN202611481609.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]本发明的目的在于提供一种离心自分层型中子吸收材料及其制备方法与应用,以解决现有常规梯度材料存在的层间界面明显、梯度不连续、烧结易开裂以及涂层型防护结构易脱落等问题
[0032]1. 梯度连续性更好:通过浆料中颗粒在离心场中的连续迁移形成径向组分梯度,Hf/(Hf+RE)摩尔比从中心至外表面连续或近连续增加,有利于降低界面应力集中。
Smart Images

Figure CN122977838A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of neutron absorbing ceramic materials, specifically relating to a centrifugally self-stratified neutron absorbing material, its preparation method, and its application. Background Technology
[0002] Rare earth oxides possess strong neutron absorption capabilities and can be considered as candidate absorbing materials for nuclear reactor control rod cores. Hafnium oxide has a high melting point, good high-temperature chemical stability, and excellent water corrosion resistance; furthermore, hafnium itself also possesses a certain neutron absorption capacity. In rare earth oxide-hafnium oxide composite systems, increasing the hafnium oxide ratio is beneficial for improving the material's water corrosion resistance and high-temperature steam stability. However, uniformly increasing the hafnium oxide content throughout the core will reduce the content of rare earth absorbing components per unit volume, thus affecting the utilization efficiency of the neutron absorbing components. If only an external surface coating is used to increase corrosion resistance, problems such as thermal expansion differences between the coating and the substrate, insufficient bonding strength, and peeling during service may arise.
[0003] To balance neutron absorption capacity and corrosion resistance, constructing gradient structure materials is a feasible approach. Conventional gradient materials typically employ layered powder loading, layered pressing, or multiple coatings to form layers of different components. While this method can macroscopically create a structure with a corrosion-resistant outer layer and an absorption inner layer, it still suffers from the following limitations:
[0004] Firstly, the gradient structure formed by conventional layered powder loading or mechanical stacking often has obvious interlayer interfaces and large abrupt changes in interlayer composition. During sintering and thermal cycling, it is prone to cracking or delamination due to differences in sintering shrinkage and thermal expansion.
[0005] Secondly, conventional gradient structures are usually discrete layered structures, making it difficult to form a smooth component gradient that changes continuously along the radial direction. This is especially true for cylindrical, long rod-shaped, or ring-shaped control rod cores, where it is difficult to control the layering accuracy, coaxiality, and shell thickness consistency.
[0006] Third, there are differences in sintering activity, reaction behavior and thermal expansion behavior between the rare earth oxide-rich region and the hafnium oxide-rich region. If the hafnium oxide content in the outer layer is simply increased, radial shrinkage gradients are easily generated and cracks are formed during the sintering stage.
[0007] Therefore, there is an urgent need for a method to prepare neutron absorbing materials that can form a hafnium oxide-rich corrosion-resistant region on the outside, while maintaining a high content of rare earth absorbing components inside, and reducing the risk of sintering cracking. Summary of the Invention
[0008] The purpose of this invention is to provide a centrifugally self-layered neutron absorbing material, its preparation method, and its application, in order to solve the problems of obvious interlayer interfaces, discontinuous gradients, easy cracking during sintering, and easy detachment of coating-type protective structures that exist in existing conventional gradient materials.
[0009] This invention utilizes the higher density of hafnium oxide powder compared to rare earth oxide powders such as Eu₂O₃, Sm₂O₃, and Dy₂O₃. In a slurry state, a centrifugal field causes the hafnium oxide powder to migrate and accumulate radially outwards, forming a radially continuous or near-continuous gradient structure material with hafnium-rich outer edges and relatively rare earth oxide-rich inner edges. Simultaneously, rare earth hafnium salt pre-reacted powder is introduced into the ceramic slurry as a chemical composition transition buffer phase. A dual-scale hafnium oxide design, combining micron-sized and nano-sized hafnium oxide powders, is employed to reduce the shrinkage difference, thermal expansion difference, and interfacial stress caused by the radial composition gradient during sintering, thereby avoiding or minimizing sintering cracking.
[0010] To achieve the above objectives, the present invention adopts the following technical solution.
[0011] A method for preparing a centrifugally self-stratified neutron absorbing material includes the following steps:
[0012] S1. Preparation of ceramic slurry, wherein the raw materials of the ceramic slurry include rare earth oxide powder, hafnium oxide powder, rare earth hafnium salt pre-reacted powder, and aqueous colloidal solution; wherein the theoretical density of rare earth oxide powder is less than that of hafnium oxide powder; the rare earth hafnium salt pre-reacted powder is a RE-Hf-O composite oxide, and its theoretical density is between that of rare earth oxide powder and hafnium oxide powder; the hafnium oxide powder includes micron-sized and nano-sized particles;
[0013] S2. After adding the ceramic slurry to the initiator, inject it into the mold and centrifuge the mold around its own axis to obtain a gradient slurry preform. The centrifugation process includes at least two stages, with a centrifugation acceleration of no more than 1200 g and a centrifugation time of no more than 15 min in any stage. The last stage also includes initiating gelation.
[0014] S3. The gradient slurry preform is gelled and solidified to obtain a wet preform;
[0015] S4. The wet blank is dried, degreased and pre-sintered to obtain a pre-sintered blank with a radial composition gradient;
[0016] S5. The pre-sintered blank is sintered to obtain a centrifugal self-stratified neutron absorbing material, wherein the difference in the Hf / (Hf+RE) molar ratio between the outer surface and the center exceeds 0.15, and the change in the Hf / (Hf+RE) molar ratio along the radial direction does not exceed 0.05 / 100μm.
[0017] The not exceeding 0.05 / 100μm mentioned here means that the change in the Hf / (Hf+RE) molar ratio within any adjacent 100 μm thickness along the radial direction does not exceed 0.05.
[0018] Optionally, the rare earth hafnium salt pre-reacted powder is prepared by the following method: rare earth oxide powder and hafnium oxide powder are mixed at a RE2O3:HfO2 molar ratio of 1:1.5 to 1:2.5, ball-milled, and then kept at 1000 to 1500℃ for 1 to 8 h; the D50 particle size of the rare earth hafnium salt pre-reacted powder is 0.3 to 3 μm.
[0019] Optionally, the D50 particle size of the micron-sized hafnium oxide powder is 0.5 to 10 μm, the D50 particle size of the nano-sized hafnium oxide powder is 20 to 300 nm, and the mass ratio of the micron-sized hafnium oxide powder to the nano-sized hafnium oxide powder is 90:10 to 70:30.
[0020] Optionally, the theoretical density difference between the rare earth oxide powder and the hafnium oxide powder is not less than 1.5 g / cm³. 3 .
[0021] Optionally, the solid volume fraction of the ceramic slurry is 45% to 60%; based on the total molar amount of solid phase, the rare earth oxide powder accounts for 5% to 45%, the hafnium oxide powder accounts for 40% to 90%, and the rare earth hafnium salt pre-reacted powder accounts for 3% to 40%.
[0022] Optionally, the centrifugation process includes three sequential stages; wherein,
[0023] In the first stage, centrifuge at a centrifugal acceleration of 50 g to 300 g for 0.5 to 5 min;
[0024] In the second stage, centrifuge at a centrifugal acceleration of 300 g to 1200 g for 1 to 15 minutes;
[0025] In the third stage, centrifugation was carried out at a centrifugal acceleration of 50 g to 300 g for 0.5 to 10 min, which simultaneously induced gelation.
[0026] Optionally, the aqueous colloidal solution contains an organic monomer and a crosslinking agent, wherein the organic monomer is acrylamide, the crosslinking agent is N,N'-methylenebisacrylamide, and the initiator is ammonium persulfate; the gelation initiation is initiated by heating.
[0027] Optionally, in step S4, before the pre-sintering, the wet blank or the dried blank is subjected to cold isostatic pressing treatment at a pressure of 100-300 MPa and a holding time of 5-20 min.
[0028] Optionally, in step S4, the pre-sintering temperature is 800–1250°C and the holding time is 1–10 h; in step S5, the sintering temperature is 1300–1700°C.
[0029] A centrifugal self-stratified neutron absorber material is prepared by the above-described preparation method; the centrifugal self-stratified neutron absorber material comprises, from the inside out, an absorber core rich in rare earth oxides, a transition region containing rare earth hafnium salts, and a corrosion-resistant outer shell rich in hafnium oxide.
[0030] The above-mentioned centrifugally self-stratified neutron-absorbing materials are used in control rod cores. Control rods are crucial components in nuclear reactors for achieving reactivity control and shutdown functions. Control rod core materials need to possess high neutron absorption capacity, good dimensional stability, high thermal stability, and chemical stability in high-temperature water or steam environments.
[0031] Compared with the prior art, the present invention has at least the following beneficial effects:
[0032] 1. Better gradient continuity: The radial component gradient is formed by the continuous migration of particles in the slurry in the centrifugal field. The Hf / (Hf+RE) molar ratio increases continuously or nearly continuously from the center to the outer surface, which is beneficial to reducing interfacial stress concentration.
[0033] 2. Higher interlayer bonding strength: The gradient structure of this invention is formed within the same slurry system, and there are no independent powder-laying interfaces between the regions after gel locking. After sintering, each region is a continuous ceramic body, and the corrosion-resistant outer shell and the absorbent core are connected through transition regions and hafnium-rich grain boundary networks, making interlayer debonding less likely to occur.
[0034] 3. More suitable for cylindrical or long rod-shaped control rods: The core of a control rod is usually cylindrical, long rod-shaped, or ring-shaped, and during service, corrosive media preferentially act from the outer surface. The centrifugal self-stratification of this invention naturally forms a radial concentric gradient, so that the hafnium-rich corrosion-resistant area is distributed on the outer side, which is the first to come into contact with high-temperature water or water vapor, and the structural design matches the service environment.
[0035] 4. Simultaneously considering neutron absorption and corrosion resistance: If the HfO2 content is uniformly increased overall, the rare earth absorbing components will be diluted. This invention arranges more HfO2 in the outer corrosion-resistant area, while retaining a higher proportion of rare earth oxides in the inner absorption area, thereby improving corrosion resistance while maintaining the utilization efficiency of the neutron absorbing components.
[0036] 5. Lower risk of sintering cracking: Abrupt compositional changes in conventional gradient cores can easily lead to poor sintering shrinkage and thermal expansion. This invention reduces the risk of sintering cracking caused by uneven compositional distribution through the combined effects of continuous or near-continuous gradients, rare earth hafnium salt pre-reacted powder buffer phases, nano-HfO2 grain boundary networks, and segmented pre-sintering and high-temperature sintering.
[0037] 6. Avoiding coating peeling: The corrosion-resistant outer shell of this invention is not a post-coating layer, but is formed in situ inside the preform through centrifugal self-delamination and is densified integrally with the core during sintering. Therefore, there is no peeling problem at the traditional coating-substrate interface between the corrosion-resistant outer shell and the internal absorbent core. Attached Figure Description
[0038] Figure 1 This is a schematic flowchart illustrating the preparation method of the centrifugally self-stratified neutron absorbing material in this embodiment.
[0039] Figure 2 This is a schematic diagram of the radial component gradient structure of the control rod core obtained by the preparation method of the embodiment.
[0040] Figure 3 The SEM morphology image and EDS line scan results of the control rod core prepared in Example 1 are shown.
[0041] Figure 4 The surface SEM image and EDS radial line scan results of the control rod core prepared for Comparative Example 4 are shown. Detailed Implementation
[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and comparative examples. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0043] refer to Figure 1 The following describes in detail the preparation method of the centrifugal self-stratified neutron absorbing material applied to the control rod core.
[0044] S1. Preparation of ceramic slurry
[0045] Rare earth oxide powder, hafnium oxide powder and rare earth hafnium salt pre-reacted powder are used as solid components, mixed with an aqueous colloidal solution containing organic monomers and crosslinking agents, and ball-milled after adding a dispersant to obtain a ceramic slurry with a solid volume fraction of 45% to 60%.
[0046] The rare earth oxide powder is selected from one or more of Eu2O3, Sm2O3, and Dy2O3, with a theoretical density of 7.0–7.9 g / cm³. 3 The theoretical density of the hafnium oxide powder is 9.5–9.7 g / cm³. 3 The theoretical density difference between hafnium oxide powder and rare earth oxide powder is not less than 1.5 g / cm³. 3 This provides a physical basis for the radial migration of particles in the subsequent centrifugal field;
[0047] The rare earth hafnium salt pre-reacted powder is a RE-Hf-O composite oxide, where RE is selected from one or more of Eu, Sm, and Dy. The theoretical density of the pre-reacted powder is between that of rare earth oxides and hafnium oxide, and it is naturally distributed in the transition region in a centrifugal field. It has good chemical compatibility with both rare earth oxides and HfO2.
[0048] Based on the total molar amount of solid phase, rare earth oxide powder accounts for 5% to 45%, hafnium oxide powder accounts for 40% to 90%, and rare earth hafnium salt pre-reacted powder accounts for 3% to 40%.
[0049] Preferably, the hafnium oxide powder comprises micron-sized hafnium oxide powder (D50 of 0.5–10 μm) and nano-sized hafnium oxide powder (D50 of 20–300 nm), with a mass ratio of 90:10 to 70:30. Micron-sized HfO2 exhibits strong radial migration driving force in a centrifugal field, primarily migrating outwards from the mold in response to the centrifugal field and accumulating into a hafnium-rich shell. Nano-sized HfO2 is strongly bound by the slurry network and is largely retained within the entire green body, forming a continuous or semi-continuous hafnium-rich grain boundary network after sintering.
[0050] Preferably, the rare earth hafnium salt pre-reacted powder is prepared by the following method: rare earth oxide powder and hafnium oxide powder are mixed at a RE2O3:HfO2 molar ratio of 1:1.5 to 1:2.5, ball-milled, and then kept at 1000-1500℃ for 1-8 h to obtain RE-Hf-O composite oxide with a D50 particle size of 0.3-3 μm. Further, the RE-Hf-O composite oxide includes RE2Hf2O7 and RE4Hf3O. 12 One or more of them.
[0051] Preferably, the organic monomer is acrylamide, the crosslinking agent is N,N'-methylenebisacrylamide, the organic monomer content accounts for 2% to 10% of the water mass in the aqueous colloidal solution, the mass ratio of organic monomer to crosslinking agent is (8 to 20):1; the pH of the aqueous colloidal solution is adjusted to 9 to 11; the dispersant is ammonium polyacrylate, and its amount accounts for 0.1% to 0.8% of the total mass of the solid phase component; the ball milling time is 16 to 24 h.
[0052] S2, segmented centrifugal drive density difference self-stratification
[0053] The ceramic slurry is injected into a cylindrical or tubular mold, an initiator is added, and the mold is rotated around its axis in a centrifugal field. The following segmented centrifugation program is used to actively utilize density differences to create a radial gradient:
[0054] (1) In the first stage, centrifuge at 50 g to 300 g for 0.5 to 5 min to allow the slurry to spread stably in the mold and form an initial radial concentration difference;
[0055] (2) In the second stage, the micron-sized hafnium oxide powder is centrifuged at 300 g to 1200 g for 1 to 15 min to allow the powder to migrate radially to the outside of the mold and accumulate into a hafnium-rich shell region. At the same time, the medium-density rare earth hafnium salt pre-reacted powder forms a transition region between the shell and the core.
[0056] (3) In the third stage, centrifuge at 50 g to 300 g for 0.5 to 10 min to induce gelation or increase the viscosity of the slurry, so as to avoid back mixing of the radial gradient formed after centrifugation stops.
[0057] The initiator is preferably ammonium persulfate, and the amount added is 2% to 4% of the mass of the organic monomer; the centrifugation temperature in the first and second stages is 20 to 40°C, and the centrifugation temperature in the third stage is 60 to 80°C, thereby initiating gelation by increasing the temperature.
[0058] S3, gelation-locked radial gradient
[0059] The gelation temperature is 40–80℃ and the time is 30–90 min. In the gelled preform, the Hf / (Hf+RE) molar ratio increases continuously or nearly continuously from the core center to the outer surface of the core, and the Hf / (Hf+RE) molar ratio on the outer surface of the core is at least 0.15 higher than that at the core center.
[0060] S4, drying, degreasing and pre-sintering
[0061] The wet blank is dried, degreased, and pre-sintered to obtain a pre-sintered blank with a radial composition gradient. Drying includes humidity-controlled drying (20–60°C, relative humidity 40%–95%, 4–72 h) and low-temperature vacuum drying (40–90°C, vacuum degree -0.05–-0.10 MPa, 2–24 h); degreasing involves heating at 0.2–2°C / min to 200–350°C and holding for 1–8 h, followed by heating at 0.2–2°C / min to 400–700°C and holding for 1–8 h; the pre-sintering temperature is 800–1250°C, and the holding time is 1–10 h.
[0062] Preferably, after gelation and locking of the radial gradient but before sintering, the wet or dry green blank can be further subjected to cold isostatic pressing at a pressure of 100–300 MPa for 5–20 min. Since the gel network has fixed the spatial distribution of particles, the cold isostatic pressing pressure is uniformly transmitted radially, which will not destroy the formed radial component gradient. On the contrary, it can increase the relative density of the green blank from about 45% during gel casting to about 58% or more, significantly reducing the volume shrinkage during subsequent high-temperature sintering and further suppressing the risk of cracking of the gradient structure during sintering.
[0063] S5, Sintering Densification
[0064] The pre-sintered green body is subjected to pressureless sintering or two-stage sintering: heating at 0.5–5℃ / min to 1300–1700℃ and holding for 2–24 h; or first heating to 1300–1500℃ and holding for 1–8 h, then heating to 1500–1700℃ and holding for 1–16 h. After sintering, hot isostatic pressing is optionally performed at 1200–1600℃ and 50–200 MPa for 0.5–6 h.
[0065] The centrifugally self-stratified neutron absorber core prepared by the above method, such as Figure 2 As shown, there is a continuous or nearly continuous Hf / (Hf+RE) molar ratio increasing gradient from the center to the outer surface in the radial direction, and it includes an absorption core rich in rare earth oxides and a rare earth hafnium salt transition region located between the two.
[0066] The outer region, defined as having an Hf / (Hf+RE) molar ratio of not less than 0.85, is considered a corrosion-resistant outer shell. This outer shell has a thickness of 15%–30% of the core radius and a relative density ≥95%. The Hf / (Hf+RE) molar ratio at the core center is 0.55–0.70, and on the outer surface, it is 0.88–0.95. The transition region contains RE-Hf-O composite oxides. The variation in the Hf / (Hf+RE) molar ratio within a radially adjacent 100 μm thickness does not exceed 0.05. Due to its moderate density, the rare earth hafnium salt pre-reacted powder exhibits a higher relative content in the transition region after centrifugation than its average content in the solid phase, indicating relative enrichment in the transition region.
[0067] Among them, by utilizing the density difference of the material itself, a radial hafnium-rich gradient is formed in the slurry state. Since it is formed by particle migration and self-organization in the same slurry system, the resulting gradient structure has better continuity and no obvious artificial interlayer interface.
[0068] RE-Hf-O composite oxide pre-reacted powder was introduced into the slurry as a sintering stress buffer phase. This pre-reacted powder exhibits good chemical compatibility with both rare earth oxides and hafnium oxide, forming a transition buffer phase between rare earth-rich and hafnium-rich regions. Its functions include reducing abrupt reaction changes between rare earth oxides and hafnium oxide; mitigating sintering shrinkage differences between different radial regions; reducing thermal expansion mismatch during cooling; minimizing circumferential and interlaminar cracks caused by abrupt compositional changes; and improving the structural integrity of the gradient core during sintering and thermal cycling.
[0069] A blend of micron-sized and nano-sized hafnium oxide powders is employed. The micron-sized powder primarily responds to the centrifugal field and migrates outwards from the mold, forming the hafnium-rich outer shell region. The nano-sized powder, due to its small particle size and strong binding effect from the slurry network, does not migrate completely to the outer surface but remains largely within the entire green body, particularly distributed in interparticle spaces and grain boundaries. After sintering, the nano-sized hafnium oxide forms a continuous or semi-continuous hafnium-rich grain boundary network, maintaining chemical and structural continuity between the absorber core, transition region, and hafnium-rich outer shell, further reducing the risk of decoupling and cracking between the hafnium-rich outer layer and the internal region.
[0070] By inducing gelation or solidification shortly after centrifugation, the viscosity of the slurry rapidly increases, thereby locking in the established radial component gradient. This design allows the centrifugally self-stratified structure to be stably transformed into a dried preform and a sintered core, preventing the gradient structure from being destroyed in subsequent processes.
[0071] The main raw materials used in the examples are as follows:
[0072] Eu2O3 powder: purity ≥99.9%, D50 particle size approximately 1.2 μm, theoretical density approximately 7.42 g / cm³. 3 ;
[0073] Sm2O3 powder: purity ≥99.9%, D50 particle size approximately 1.0 μm, theoretical density approximately 7.07 g / cm³. 3 ;
[0074] Dy2O3 powder: purity ≥99.9%, D50 particle size approximately 1.1 μm, theoretical density approximately 7.81 g / cm³. 3 ;
[0075] Micron-sized HfO2 powder (m-HfO2): purity ≥99.9%, D50 particle size approximately 2.0 μm, theoretical density approximately 9.68 g / cm³. 3 ;
[0076] Nanoscale HfO2 powder (n-HfO2): purity ≥99.9%, D50 particle size approximately 80 nm, theoretical density approximately 9.68 g / cm³. 3 ;
[0077] Acrylamide (AM): Chemically pure, content ≥99%;
[0078] N,N'-Methylenebisacrylamide (MBAM): Chemically pure, content ≥99%;
[0079] Ammonium polyacrylate (PAA-NH4) dispersant: solid content 40%;
[0080] Ammonium persulfate (APS) initiator: analytical grade;
[0081] Ammonia solution: analytical grade, mass fraction 25%–28%, diluted to a 10% aqueous solution for pH adjustment before use.
[0082] There is a minimum concentration of 1.87 g / cm³ between HfO₂ and the aforementioned rare earth oxides. 3 The density difference provides sufficient physical driving force for centrifugal self-stratification.
[0083] Example 1
[0084] A method for preparing a centrifugally self-stratified neutron absorber core in an Eu2O3-HfO2 system includes the following steps.
[0085] 1. Preparation of rare earth hafnium salt pre-reacted powder (Eu-Hf-O)
[0086] Weigh 17.59 g (0.05 mol) of Eu2O3 powder and 21.06 g (0.10 mol) of HfO2 powder according to a molar ratio of Eu2O3:HfO2 of 1:2.0. Add 100 mL of anhydrous ethanol and ball mill with ZrO2 grinding balls as the grinding medium (ball-to-powder mass ratio 5:1) at 300 r / min for 6 h. After drying, heat to 1300℃ in an alumina crucible under air atmosphere at 5℃ / min and hold for 4 h. After natural cooling, ball mill again to crush and pass through a 200-mesh sieve to obtain Eu-Hf-O composite oxide pre-reaction powder containing the Eu2Hf2O7 phase (D50 approximately 1.0 μm, theoretical density approximately 8.36 g / cm³). 3 (It is located between Eu2O3 and HfO2). XRD characterization revealed that the main phase of this powder is a defective fluorite structure Eu2Hf2O7.
[0087] 2. Preparation of premixed colloidal solutions
[0088] Add 0.96 g acrylamide (AM) and 0.080 g N,N'-methylenebisacrylamide (MBAM, AM / MBAM mass ratio 12:1) to 20 mL of deionized water, stir magnetically for 30 min until completely dissolved, adjust the pH to 10.0 with 10% ammonia, and sonicate for 10 min to remove bubbles to obtain a clear premixed colloidal solution.
[0089] 3. Preparation of ceramic slurry
[0090] The ingredients are prepared according to the solid-phase molar ratio of Eu₂O₃ : HfO₂ : Eu-Hf-O = 18% : 70% : 12% (total 100%), wherein the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 80:20. Specific additions: Eu2O3 powder: 6.34 g
[0091] m-HfO2 powder: 12.85 g
[0092] n-HfO2 powder: 3.21 g,
[0093] Eu-Hf-O pre-reaction powder: 4.94 g;
[0094] The above powder was added to a premixed colloidal solution, and 0.108 g of ammonium polyacrylate (0.4% of the total mass of ceramic powder) was added as a dispersant. An appropriate amount of deionized water was then added to adjust the solid volume fraction to 50%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 350 mPa·s (shear rate 100 s⁻¹). -1 ).
[0095] 4. Segmented centrifugation shaping and gelation locking
[0096] Add 0.038 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0097] First stage: Centrifuge at 200 g for 3 min (room temperature 25℃) to allow the slurry to spread steadily radially within the mold and form an initial concentration gradient;
[0098] Second stage: Centrifugation at 800 g for 10 min (room temperature 25℃). Micron-sized HfO2 migrated radially towards the outside of the mold and accumulated under the drive of density difference, with a medium density (approximately 8.36 g / cm³). 3 The migration rate of Eu-Hf-O pre-reacted powder is between that of HfO2 and Eu2O3, and it is naturally distributed in the transition zone; the migration rate of nano-sized HfO2 is slower due to the binding of the gel network precursor and the influence of Brownian motion, and it is mostly retained in the entire body of the preform.
[0099] Third stage: The centrifuge chamber temperature is raised to 70℃ and maintained, while the temperature is simultaneously reduced to 150 g and centrifuged for 5 min. In this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the established radial gradient is fixed in the gel network.
[0100] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 45 minutes to complete gel solidification and obtain a wet blank.
[0101] 5. Cold isostatic pressing
[0102] The wet billet with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. Before cold isostatic pressing, the relative density of the wet billet was about 46%, and after isostatic pressing, the relative density increased to about 59%, and the radial gradient did not change significantly.
[0103] 6. Drying, degreasing, and pre-sintering
[0104] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0105] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0106] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0107] 600℃ to 1000℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0108] Let it cool naturally to room temperature.
[0109] A pre-sintered green body with a radial composition gradient was obtained, with a relative density of approximately 65%.
[0110] 7. Sintering densification
[0111] The pre-sintered green body was sintered in a sintering furnace under an Ar atmosphere in the following two stages:
[0112] From room temperature to 1450℃: heating rate 3℃ / min, hold for 4 h;
[0113] 1450℃ to 1650℃: heating rate 2℃ / min, holding for 8 h;
[0114] Let it cool naturally to room temperature.
[0115] Depend on Figure 3 It is evident that the core surface is dense and free of obvious pores and cracks. EDS radial line scan results show that the Hf element content increases continuously from the core center to the outer surface, while the Eu element content decreases continuously accordingly. The Hf / (Hf+Eu) molar ratio increases gradually from about 0.62 at the center to about 0.91 at the outer surface, with a variation of no more than 0.05 within adjacent 100 μm, indicating the formation of a continuous and gentle radial hafnium-rich gradient.
[0116] Example 2
[0117] A method for preparing a centrifugally self-stratified neutron absorber core in an Sm2O3-HfO2 system includes the following steps.
[0118] 1. Preparation of rare earth hafnium salt pre-reacted powder (Sm-Hf-O)
[0119] Weigh 17.42 g (0.05 mol) of Sm₂O₃ powder and 21.06 g (0.10 mol) of HfO₂ powder at a molar ratio of 1:2.0. Add 100 mL of anhydrous ethanol and ball mill at 300 r / min for 6 h using ZrO₂ grinding balls as the grinding medium (ball-to-powder mass ratio 5:1). After drying, heat to 1350 °C at 5 °C / min and hold for 4 h in an alumina crucible under air atmosphere. After natural cooling, ball mill again to crush and pass through a 200-mesh sieve to obtain a pre-reacted Sm-Hf-O composite oxide powder containing the Sm₂Hf₂O₇ phase (D50 approximately 0.9 μm, theoretical density between Sm₂O₃ and HfO₂). XRD characterization showed that the main phase of the powder was defective fluorite structure Sm₂Hf₂O₇.
[0120] 2. Preparation of premixed colloidal solutions
[0121] Add 1.00 g acrylamide (AM) and 0.091 g N,N'-methylenebisacrylamide (MBAM, AM / MBAM mass ratio 11:1) to 20 mL of deionized water, stir magnetically for 30 min until completely dissolved, adjust the pH to 10.5 with 10% ammonia, and sonicate for 10 min to remove bubbles to obtain a clear premixed colloidal solution.
[0122] 3. Preparation of ceramic slurry
[0123] The ingredients are prepared according to the solid-phase molar ratio of Sm₂O₃ : HfO₂ : Sm-Hf-O = 20% : 65% : 15% (total 100%), wherein the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 75:25. Specific additions:
[0124] Sm2O3 powder: 7.10 g,
[0125] m-HfO2 powder: 11.41 g
[0126] n-HfO2 powder: 3.80 g
[0127] Sm-Hf-O pre-reacted powder: 6.15 g;
[0128] The above powder was added to a premixed colloidal solution, and 0.142 g of ammonium polyacrylate (0.5% of the total mass of ceramic powder) was added as a dispersant. An appropriate amount of deionized water was then added to adjust the solid volume fraction to 55%. The mixture was ball-milled at 240 r / min for 20 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 420 mPa·s (shear rate 100 s⁻¹). -1 ).
[0129] 4. Segmented centrifugation and gelation
[0130] Add 0.040 g of ammonium persulfate (4% of AM by mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0131] First stage: Centrifuge at 250 g for 2 min (room temperature 25℃) to allow the slurry to spread steadily radially within the mold and form an initial concentration gradient;
[0132] Second stage: Centrifuge at 1000 g for 8 min (room temperature 25℃). Micron-sized HfO2 migrates radially towards the outside of the mold and accumulates under the drive of density difference. Sm-Hf-O pre-reaction powder is distributed in the transition zone.
[0133] Third stage: The centrifuge chamber temperature is raised to 70℃ and maintained, while the temperature is simultaneously reduced to 200 g and centrifuged for 4 min. During this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the established radial gradient is fixed in the gel network.
[0134] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 60 minutes to complete gel solidification and obtain a wet blank.
[0135] 5. Cold isostatic pressing
[0136] The wet preform with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 250 MPa for 5 min. After cold isostatic pressing, the density of the wet preform was significantly increased, and the radial composition gradient remained stable.
[0137] 6. Drying, degreasing, and pre-sintering
[0138] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0139] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0140] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0141] 600℃ to 1150℃: heating rate 3℃ / min, holding for 3 h (pre-sintering);
[0142] Let it cool naturally to room temperature.
[0143] A pre-sintered green body with a radial composition gradient is obtained.
[0144] 7. Sintering densification
[0145] The pre-sintered green body was sintered in a sintering furnace under an Ar atmosphere in the following two stages:
[0146] From room temperature to 1500℃: heating rate 3℃ / min, hold for 4 h;
[0147] 1500℃ to 1680℃: heating rate 2℃ / min, holding time 6 h;
[0148] Let it cool naturally to room temperature.
[0149] Example 3
[0150] A method for preparing a centrifugally self-stratified neutron absorber core in a Dy2O3-HfO2 system includes the following steps.
[0151] 1. Preparation of rare earth hafnium salt pre-reacted powder (Dy-Hf-O)
[0152] Weigh 18.64 g (0.05 mol) of Dy2O3 powder and 23.17 g (0.11 mol) of HfO2 powder at a Dy2O3:HfO2 molar ratio of 1:2.2. Add 100 mL of anhydrous ethanol and ball mill at 300 r / min for 6 h using ZrO2 grinding balls as the grinding medium (ball-to-powder mass ratio 5:1). After drying, heat to 1400℃ at 5℃ / min and hold for 5 h in an alumina crucible under air atmosphere. After natural cooling, ball mill again to crush and pass through a 200-mesh sieve to obtain a Dy-Hf-O composite oxide pre-reaction powder containing the Dy2Hf2O7 phase (D50 approximately 1.1 μm, theoretical density between Dy2O3 and HfO2). XRD characterization showed that the main phase of the powder was defective fluorite structure Dy2Hf2O7.
[0153] 2. Preparation of premixed colloidal solutions
[0154] Add 0.88 g acrylamide (AM) and 0.059 g N,N'-methylenebisacrylamide (MBAM, AM / MBAM mass ratio 15:1) to 20 mL of deionized water, stir magnetically for 30 min until completely dissolved, adjust the pH to 9.5 with 10% ammonia, and sonicate for 10 min to remove bubbles to obtain a clear premixed colloidal solution.
[0155] 3. Preparation of ceramic slurry
[0156] The ingredients are prepared according to a solid-phase molar ratio of Dy₂O₃ : HfO₂ : Dy-Hf-O = 15% : 75% : 10% (total 100%), wherein the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 85:15. Specific additions:
[0157] Dy2O3 powder: 6.45 g,
[0158] m-HfO2 powder: 14.64 g
[0159] n-HfO2 powder: 2.58 g
[0160] Dy-Hf-O pre-reacted powder: 4.38 g;
[0161] The above powder was added to a premixed colloidal solution, and 0.084 g of ammonium polyacrylate (0.3% of the total mass of ceramic powder) was added as a dispersant. Then, an appropriate amount of deionized water was added to adjust the solid volume fraction to 52%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 360 mPa·s (shear rate 100 s⁻¹). -1 ).
[0162] 4. Segmented centrifugation shaping and gelation locking
[0163] Add 0.035 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0164] First stage: Centrifuge at 150 g for 2 min (room temperature 25℃) to allow the slurry to spread steadily radially in the mold and form an initial concentration gradient;
[0165] Second stage: Centrifuge at 1200 g for 12 min (room temperature 25℃). Micron-sized HfO2 migrates radially towards the outside of the mold and accumulates under the drive of density difference. Dy-Hf-O pre-reaction powder is distributed in the transition zone.
[0166] Third stage: The centrifuge chamber temperature is raised to 70℃ and maintained, while the temperature is lowered to 200 g and centrifuged for 3 min. In this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the radial gradient that has been formed is fixed in the gel network.
[0167] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 45 minutes to complete gel solidification and obtain a wet blank.
[0168] 5. Cold isostatic pressing
[0169] The wet preform with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. After cold isostatic pressing, the density of the wet preform increased, and the radial gradient was not destroyed.
[0170] 6. Drying, degreasing, and pre-sintering
[0171] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0172] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0173] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0174] 600℃ to 1100℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0175] Let it cool naturally to room temperature.
[0176] A pre-sintered green body with a radial composition gradient is obtained.
[0177] 7. Sintering densification
[0178] The pre-sintered green body was sintered in a sintering furnace under an Ar atmosphere in the following two stages:
[0179] From room temperature to 1450℃: heating rate 3℃ / min, hold for 3 h;
[0180] 1450℃ to 1700℃: heating rate 2℃ / min, holding for 4 h;
[0181] Let it cool naturally to room temperature.
[0182] Example 4
[0183] A method for preparing a centrifugally self-stratified neutron absorber core in the Eu2O3-Dy2O3-HfO2 system includes the following steps.
[0184] 1. Preparation of rare earth hafnium salt pre-reacted powder [(Eu,Dy)-Hf-O]
[0185] Weigh 8.80 g of Eu₂O₃ powder, 9.32 g of Dy₂O₃ powder, and 21.06 g of HfO₂ powder according to a molar ratio of Eu₂O₃:Dy₂O₃:HfO₂ of 0.5:0.5:2.0. Add 100 mL of anhydrous ethanol and ball mill at 300 r / min for 6 h using ZrO₂ grinding balls as the grinding medium (ball-to-powder mass ratio 5:1). After drying, heat to 1400 °C at 5 °C / min and hold for 4 h in an alumina crucible under air atmosphere. After natural cooling, ball mill again to crush and pass through a 200-mesh sieve to obtain a (Eu,Dy)-Hf-O composite oxide pre-reaction powder containing a (Eu,Dy)₂Hf₂O₇ solid solution phase (D50 approximately 1.0 μm). XRD characterization showed that the main phase of the powder was a defective fluorite structure (Eu,Dy)₂Hf₂O₇ solid solution.
[0186] 2. Preparation of premixed colloidal solutions
[0187] Add 0.96 g acrylamide (AM) and 0.080 g N,N'-methylenebisacrylamide (MBAM, AM / MBAM mass ratio 12:1) to 20 mL of deionized water, stir magnetically for 30 min until completely dissolved, adjust the pH to 10.0 with 10% ammonia, and sonicate for 10 min to remove bubbles to obtain a clear premixed colloidal solution.
[0188] 3. Preparation of ceramic slurry
[0189] The ingredients are prepared according to the solid-phase molar ratio (Eu₂O₃ + Dy₂O₃): HfO₂: (Eu,Dy)-Hf-O = 20% : 68% : 12% (total 100%), wherein Eu₂O₃ and Dy₂O₃ are mixed in an equimolar ratio, and the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 80:20. Specific additions:
[0190] Eu2O3 powder: 3.52 g
[0191] Dy2O3 powder: 3.73 g,
[0192] m-HfO2 powder: 12.49 g
[0193] n-HfO2 powder: 3.12 g,
[0194] (Eu,Dy)-Hf-O pre-reacted powder: 4.95 g;
[0195] The above powder was added to a premixed colloidal solution, and 0.111 g of ammonium polyacrylate (0.4% of the total mass of ceramic powder) was added as a dispersant. An appropriate amount of deionized water was then added to adjust the solid volume fraction to 50%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 360 mPa·s (shear rate 100 s⁻¹). -1 ).
[0196] 4. Segmented centrifugation shaping and gelation locking
[0197] Add 0.038 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0198] First stage: Centrifuge at 200 g for 3 min (room temperature 25℃) to allow the slurry to spread steadily radially within the mold and form an initial concentration gradient;
[0199] Second stage: Centrifuge at 900 g for 10 min (room temperature 25℃). Micron-sized HfO2 migrates radially towards the outside of the mold and accumulates under the drive of density difference. (Eu,Dy)-Hf-O pre-reaction powder is distributed in the transition zone.
[0200] Third stage: The centrifuge chamber temperature is raised to 70℃ and maintained, while the temperature is lowered to 200 g and centrifuged for 3 min. In this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the radial gradient that has been formed is fixed in the gel network.
[0201] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 45 minutes to complete gel solidification and obtain a wet blank.
[0202] 5. Cold isostatic pressing
[0203] The wet preform with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. After cold isostatic pressing, the density of the wet preform increased, and the radial gradient remained stable.
[0204] 6. Drying, degreasing, and pre-sintering
[0205] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0206] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0207] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0208] 600℃ to 1100℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0209] Let it cool naturally to room temperature.
[0210] A pre-sintered green body with a radial composition gradient is obtained.
[0211] 7. Sintering densification
[0212] The pre-sintered green body was sintered in a sintering furnace under an Ar atmosphere in the following two stages:
[0213] From room temperature to 1450℃: heating rate 3℃ / min, hold for 4 h;
[0214] 1450℃ to 1650℃: heating rate 2℃ / min, holding for 8 h;
[0215] Let it cool naturally to room temperature.
[0216] Comparative Example 1
[0217] A method for preparing a neutron absorber core in a uniformly mixed Eu2O3-HfO2 system includes the following steps.
[0218] 1. Preparation of ceramic slurry
[0219] The ingredients are prepared according to a solid-phase molar ratio of Eu₂O₃ : HfO₂ = 30% : 70% (total 100%), wherein the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 80:20. Specific additions:
[0220] Eu2O3 powder: 10.56 g
[0221] m-HfO2 powder: 12.90 g
[0222] n-HfO2 powder: 3.22 g;
[0223] The above powder was added to a premixed colloidal solution, and 0.107 g of ammonium polyacrylate (0.4% of the total mass of ceramic powder) was added as a dispersant. Then, an appropriate amount of deionized water was added to adjust the solid volume fraction to 50%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 355 mPa·s (shear rate 100 s⁻¹). -1 ).
[0224] 2. Gel injection molding
[0225] The ceramic slurry was added to 0.038 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) and stirred rapidly for 1 min. The mixture was then poured into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold were sealed). In this comparative example, no centrifugation was performed; instead, the slurry after molding was directly placed in a 70℃ constant temperature oven for 60 min to initiate AM polymerization and complete gel solidification, resulting in a uniform wet preform.
[0226] 3. Cold isostatic pressing
[0227] The wet billet with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. After cold isostatic pressing, the density of the wet billet increased, but since it did not undergo centrifugal self-stratification, the component distribution in each radial position inside the billet was basically the same.
[0228] 4. Drying, degreasing, and pre-sintering
[0229] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0230] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0231] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0232] 600℃ to 1000℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0233] Let it cool naturally to room temperature.
[0234] 5. Sintering densification
[0235] The pre-sintered green body was placed in an air atmosphere sintering furnace, heated to 1550℃ at 3℃ / min and held for 6 h, and then naturally cooled to room temperature to obtain a uniformly mixed control rod core.
[0236] Comparative Example 2
[0237] A method for preparing a neutron absorber core in an Eu2O3-HfO2 system without rare earth hafnium salt pre-reacted powder includes the following steps.
[0238] 1. Preparation of ceramic slurry
[0239] The ingredients are prepared according to a solid-phase molar ratio of Eu₂O₃ : HfO₂ = 30% : 70% (total 100%), wherein the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 80:20. Specific additions:
[0240] Eu2O3 powder: 10.56 g
[0241] m-HfO2 powder: 12.90 g
[0242] n-HfO2 powder: 3.22 g;
[0243] The above powder was added to a premixed colloidal solution, and 0.107 g of ammonium polyacrylate (0.4% of the total mass of ceramic powder) was added as a dispersant. Then, an appropriate amount of deionized water was added to adjust the solid volume fraction to 50%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 345 mPa·s (shear rate 100 s⁻¹). -1 ).
[0244] 2. Segmented centrifugation molding and gelation locking
[0245] Add 0.038 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0246] First stage (spreading stage): Centrifuge at 200 g for 3 min (room temperature 25℃) to allow the slurry to spread steadily radially in the mold and form an initial concentration gradient;
[0247] Second stage (migration stage): Centrifuge at 800 g for 10 min (room temperature 25℃). Micron-sized HfO2 migrates radially to the outside of the mold and accumulates under the drive of density difference. Since the system does not contain Eu-Hf-O pre-reacted powder with medium density and composition, there is no chemical composition transition layer between the Eu2O3 enrichment area and the HfO2 enrichment area.
[0248] The third stage (locking stage): The centrifuge chamber temperature is raised to 70°C and held at that temperature, while simultaneously being centrifuged at 150 g for 5 min. During this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the already formed radial gradient is locked by the gel network.
[0249] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 45 minutes to complete gel solidification and obtain a wet blank.
[0250] 3. Cold isostatic pressing
[0251] The wet preform with mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. After cold isostatic pressing, the density of the wet preform increased, and the radial layered structure was still maintained, but there was a lack of intermediate buffer phase between different regions.
[0252] 4. Drying, degreasing, and pre-sintering
[0253] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0254] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0255] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0256] 600℃ to 1000℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0257] Let it cool naturally to room temperature.
[0258] 5. Sintering densification
[0259] The pre-sintered green body was placed in an air atmosphere sintering furnace, heated to 1550℃ at 3℃ / min and held for 6 h, and then naturally cooled to room temperature to obtain a centrifugal layered control rod core without pre-reactive transition phase.
[0260] Comparative Example 3
[0261] A method for preparing a neutron absorber core in the Eu2O3-HfO2-Eu-Hf-O system using only micron-sized HfO2 powder includes the following steps.
[0262] 1. Preparation of rare earth hafnium salt pre-reacted powder (Eu-Hf-O)
[0263] Eu₂O₃ powder and HfO₂ powder were mixed at a molar ratio of Eu₂O₃:HfO₂ of 1:2. The mixture was then ball-milled in a zirconia ball mill with anhydrous ethanol for 12 h. After drying, the mixture was placed in an air atmosphere furnace and heated to 1350℃ at a rate of 5℃ / min, held for 4 h, and then allowed to cool naturally. The mixture was then lightly pulverized and passed through a 200-mesh sieve to obtain Eu-Hf-O pre-reaction powder with a D50 particle size of approximately 1.1 μm and a theoretical density of approximately 8.36 g / cm³. 3 .
[0264] 2. Preparation of ceramic slurry
[0265] The ingredients are prepared according to the solid-phase molar ratio of Eu₂O₃ : HfO₂ : Eu-Hf-O = 25% : 60% : 15% (total 100%), where all HfO₂ is micron-sized powder. Specific additions:
[0266] Eu2O3 powder: 8.80 g
[0267] m-HfO2 powder: 13.76 g
[0268] Eu-Hf-O pre-reacted powder: 6.15 g;
[0269] The above powder was added to a premixed colloidal solution, and 0.115 g of ammonium polyacrylate (0.4% of the total mass of ceramic powder) was added as a dispersant. An appropriate amount of deionized water was then added to adjust the solid volume fraction to 50%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 330 mPa·s (shear rate 100 s⁻¹). -1 ).
[0270] 3. Segmented centrifugation molding and gelation locking
[0271] Add 0.038 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0272] First stage (spreading stage): Centrifuge at 200 g for 3 min (room temperature 25℃) to allow the slurry to spread steadily radially in the mold and form an initial concentration gradient;
[0273] Second stage (migration stage): Centrifuge at 800 g for 10 min (room temperature 25℃). Since the system contains only micron-sized HfO2, the particles respond more strongly in the centrifugation field. The HfO2 migrates faster radially to the outside of the mold, resulting in a more obvious formation of the outer hafnium-rich shell, but the gradient transition region becomes relatively narrower.
[0274] The third stage (locking stage): The centrifuge chamber temperature is raised to 70°C and held at that temperature, while simultaneously being centrifuged at 150 g for 5 min. During this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the already formed radial gradient is locked by the gel network.
[0275] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 45 minutes to complete gel solidification and obtain a wet blank.
[0276] 4. Cold isostatic pressing
[0277] The wet preform with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. After cold isostatic pressing, the density of the wet preform increased, and the radial delamination structure was preserved.
[0278] 5. Drying, degreasing, and pre-sintering
[0279] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0280] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0281] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0282] 600℃ to 1000℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0283] Let it cool naturally to room temperature.
[0284] 6. Sintering densification
[0285] The pre-sintered green body was placed in an air atmosphere sintering furnace, heated to 1550℃ at 3℃ / min and held for 6 h, and then naturally cooled to room temperature to obtain a centrifugally self-stratified control rod core using only micron-sized HfO2 powder.
[0286] Comparative Example 4
[0287] A method for preparing a neutron absorber core in the Eu2O3-HfO2-Eu-Hf-O system that forms an excessively large gradient slope by increasing centrifugal migration intensity includes the following steps.
[0288] 1. Preparation of rare earth hafnium salt pre-reacted powder (Eu-Hf-O)
[0289] Eu₂O₃ powder and HfO₂ powder were mixed at a molar ratio of Eu₂O₃:HfO₂ of 1:2. The mixture was then ball-milled in a zirconia ball mill with anhydrous ethanol for 12 h. After drying, the mixture was placed in an air atmosphere furnace and heated to 1350℃ at a rate of 5℃ / min, held for 4 h, and then allowed to cool naturally. The mixture was then lightly pulverized and passed through a 200-mesh sieve to obtain Eu-Hf-O pre-reaction powder with a D50 particle size of approximately 1.1 μm and a theoretical density of approximately 8.36 g / cm³. 3 .
[0290] 2. Preparation of ceramic slurry
[0291] The ingredients are prepared according to a solid-phase molar ratio of Eu₂O₃ : HfO₂ : Eu-Hf-O = 25% : 60% : 15% (total 100%), wherein the HfO₂ powder consists of micron-sized and nano-sized particles in a mass ratio of 80:20. Specific additions:
[0292] Eu2O3 powder: 8.80 g
[0293] m-HfO2 powder: 11.01 g,
[0294] n-HfO2 powder: 2.75 g
[0295] Eu-Hf-O pre-reacted powder: 6.15 g;
[0296] The above powder was added to a premixed colloidal solution, and 0.115 g of ammonium polyacrylate (0.4% of the total mass of ceramic powder) was added as a dispersant. An appropriate amount of deionized water was then added to adjust the solid volume fraction to 50%. The mixture was ball-milled at 240 r / min for 18 h to obtain a uniformly dispersed ceramic slurry with a viscosity of approximately 350 mPa·s (shear rate 100 s⁻¹). -1 ).
[0297] 3. Segmented centrifugation molding and gelation locking
[0298] Add 0.038 g of ammonium persulfate (4% of AM mass, pre-dissolved in 0.5 mL of deionized water) to the ceramic slurry and stir rapidly for 1 min. Pour the mixture into a cylindrical PTFE mold with an inner diameter of φ20 mm and a length of 80 mm (the bottom and top of the mold are sealed). Fix the mold on a horizontal rotor centrifuge and centrifuge according to the following three-stage procedure:
[0299] First stage (spreading stage): Centrifuge at 300 g for 5 min (room temperature 25℃) to create a more obvious initial radial concentration difference in the slurry within the mold;
[0300] Second stage (migration stage): Centrifugation at 1200 g for 20 min (room temperature 25℃). Under higher centrifugal force and longer reaction time, micron-sized HfO2 migrates more fully and is significantly enriched radially towards the outside of the mold. Eu-Hf-O pre-reaction powder is mainly distributed in a narrower transition zone, and the system as a whole forms a steeper radial composition gradient.
[0301] The third stage (locking stage): The centrifuge chamber temperature is raised to 70°C and maintained at that temperature, while simultaneously being centrifuged at 300 g for 10 min. During this stage, ammonium persulfate begins to decompose, initiating AM polymerization. The slurry viscosity increases rapidly, and the steep radial gradient that has already formed is locked by the gel network.
[0302] After centrifugation, the mold is removed as a whole and placed in a 70℃ constant temperature oven for 45 minutes to complete gel solidification and obtain a wet blank.
[0303] 4. Cold isostatic pressing
[0304] The wet preform with the mold was sealed in a vacuum bag and then subjected to cold isostatic pressing at 200 MPa for 15 min. After cold isostatic pressing, the density of the wet preform increased, and the radial composition gradient formed was still retained.
[0305] 5. Drying, degreasing, and pre-sintering
[0306] After demolding, the green body was first moist-dried at 40℃ and 80% relative humidity for 48 hours, and then vacuum-dried at 60℃ and -0.08MPa for 12 hours until the weight loss stabilized. Then, it was degreased and pre-sintered according to the following procedure:
[0307] From room temperature to 300℃: heating rate 1℃ / min, hold for 4 h;
[0308] 300℃ to 600℃: heating rate 1℃ / min, hold for 4 h;
[0309] 600℃ to 1000℃: heating rate 3℃ / min, holding for 4 h (pre-sintering);
[0310] Let it cool naturally to room temperature.
[0311] 6. Sintering densification
[0312] The pre-sintered green body was placed in an air atmosphere sintering furnace, heated to 1550℃ at 3℃ / min and held for 6 h, and then naturally cooled to room temperature to obtain a centrifugally self-stratified control rod core with a high gradient slope.
[0313] Radial line scan analysis by SEM-EDS showed that... Figure 4 It is evident that while the Hf / (Hf+RE) molar ratio in the core maintains an increasing trend from the center to the outer surface, the transition zone becomes significantly narrower. Locally, the Hf / (Hf+RE) molar ratio variation exceeds 0.05 within a 100 μm thickness, and the compositional difference between the outer surface and the center is significantly higher than in Example 1. After sintering, multiple radial and circumferential cracks appeared between the hafnium-rich outer layer and the internal region, with some cracks penetrating the transition zone. After three thermal cycles from room temperature to 1000℃, the cracks further propagated, and localized outer layer peeling occurred.
[0314] The control rod cores prepared in the above embodiments and comparative examples were characterized as follows:
[0315] 1. Microstructure characterization: The surface compactness, pore distribution and interlayer interface state were observed using scanning electron microscopy (SEM); the radial distribution of Hf and RE elements was analyzed using energy dispersive spectroscopy (EDS).
[0316] 2. Relative density: determined using Archimedes' water displacement method.
[0317] 3. Mechanical properties: The compressive strength was tested using a universal testing machine (sample size Ø6 mm × 9 mm, loading rate 0.5 mm / min); the Vickers hardness was tested using a micro Vickers hardness tester (load 9.8 N, hold for 15 s).
[0318] 4. Corrosion resistance: The samples were corroded in deionized water at 360℃ and 18.6 MPa for 14 days using a high-temperature and high-pressure reactor, and the rate of change in sample mass was measured.
[0319] 5. High-temperature oxidation performance: The samples were etched in a tubular sintering furnace at 1200℃ under a steam environment for 2 hours, and the rate of change in sample mass was measured.
[0320] 6. The percentage of the core radius to which the hafnium oxide-rich corrosion-resistant outer shell thickness is defined as:
[0321] Shell thickness as a percentage of radius (%) = t / R × 100%;
[0322] The thickness of the outermost continuous region, measured from the outer surface of the core along the radial direction towards the center of the core, that satisfies the condition that the molar ratio of Hf / (Hf+RE) is not less than 0.85, is denoted as t; the average radius of the core from the center to the outer surface is denoted as R.
[0323] Table 1. Density and gradient structure parameters of each embodiment and comparative example.
[0324]
[0325] Table 2 Mechanical corrosion resistance properties of each embodiment and comparative example
[0326]
[0327] As shown in Tables 1 and 2, Examples 1-4 all yielded control rod cores with high density, reasonable outer shell thickness, and continuous radial composition gradients, forming a radial gradient structure that gradually enriches in hafnium from the core center to the outer surface. Meanwhile, the outer shell thickness in Examples 1-4 accounted for 20%-24% of the core radius, and the maximum gradient slope was 0.032-0.036 / 100 μm, indicating that the gradient structure obtained by this invention not only forms a hafnium-rich outer layer but also has a relatively smooth transition.
[0328] In terms of mechanical and corrosion resistance, the compressive strength of Examples 1-4 was 598-625 MPa, the Vickers hardness was 1072-1094 HV1, and the corrosion weight gain was 0.39-0.46 mg·cm⁻¹. -2 The oxidative weight gain rate was 0.29–0.35 mg·cm³. -2 This demonstrates good overall performance. It indicates that the invention employs a centrifugally self-layered radial gradient structure, which can improve the core's stability in corrosive and oxidizing environments while maintaining high density and good mechanical properties.
[0329] The relative density of Comparative Example 1 was 95.9%, similar to that of the Example. This sample did not form a significant radial gradient structure, and the corrosion weight gain and oxidation weight gain rates reached 0.85 mg·cm³. -2 and 0.67 mg·cm -2 The values were all significantly higher than those in Examples 1-4. This result indicates that even with high density, the corrosion resistance and oxidation resistance of the sample are still significantly insufficient without the formation of a hafnium-rich outer shell and a continuous radial gradient, suggesting the necessity of constructing a radial gradient structure with a hafnium-rich outer shell and a relatively rare earth-rich inner shell.
[0330] The relative density of Comparative Example 2 was 92.2%, significantly lower than that of Examples 1-4. Its Hf / (Hf+RE) molar ratios at the center and outer surface were 0.40 and 0.85, respectively, with the outer shell thickness accounting for 25% of the core radius. The maximum gradient slope was 0.071 / 100 μm. Because the system lacked Eu-Hf-O pre-reacted powder with moderate density and composition, a chemical composition transition layer was missing between the Eu2O3-rich region and the HfO2-rich region. Therefore, compared to the examples, Comparative Example 2 had a larger gradient slope and lower density, with a compressive strength of 462 MPa and a Vickers hardness of 986 HV1, both inferior to the examples. This result indicates that the lack of a chemical composition transition layer leads to a steeper radial composition change and insufficient overall densification, significantly reducing mechanical properties, corrosion resistance, and oxidation resistance, which is detrimental to obtaining a control rod core with balanced performance.
[0331] When Comparative Example 3 sample used only micron-sized HfO2, the particles migrated too much outward under the centrifugal field, resulting in an excessively large gradient slope, which increased the risk of cracking during sintering and thermal cycling. Simultaneously, due to the lack of continuous distribution of nano-sized HfO2 at grain boundaries and between particles, the chemical and structural continuity between the outer and inner layers was insufficient. Therefore, the relative density measured in Comparative Example 3 was 92.8%, the compressive strength was 495 MPa, and the Vickers hardness was 898 HV1, significantly lower than the overall levels of the examples.
[0332] The excessive intensity and duration of the centrifugal migration stage in Comparative Example 4 resulted in an overly steep radial gradient slope, leading to increased sintering shrinkage and thermal stress concentration, which induced crack formation. This resulted in a measured relative density of only 93.5% and a compressive strength decrease to 448 MPa. These results indicate that when the radial composition gradient is too large, even with further increases in the hafnium enrichment of the outer layer, it is difficult to obtain better overall performance, demonstrating the necessity of reasonable control over the gradient slope.
[0333] As can be seen from Tables 1 and 2, Examples 1-4 of the present invention achieve a good balance between relative density, gradient structural parameters, mechanical properties, and corrosion resistance and oxidation resistance. Compared with Comparative Example 1, the examples significantly improve corrosion resistance and oxidation resistance by constructing a continuous radial hafnium-rich gradient; compared with Comparative Examples 2-4, the examples have a lower maximum gradient slope, indicating that a gentler gradient transition is more conducive to obtaining better overall performance. This demonstrates that the centrifugal self-stratified neutron absorber material design proposed in this invention can effectively coordinate the relationship between outer layer corrosion resistance, internal component distribution, and overall performance, thereby obtaining a control rod core with superior performance.
[0334] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art to the types of raw materials, powder particle size, slurry system, centrifugation process, gelation method, sintering process, and core shape within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a centrifugally self-stratified neutron absorbing material, characterized in that, Includes the following steps: S1. Preparation of ceramic slurry, wherein the raw materials of the ceramic slurry include rare earth oxide powder, hafnium oxide powder, rare earth hafnium salt pre-reacted powder, and aqueous colloidal solution; wherein the theoretical density of rare earth oxide powder is less than that of hafnium oxide powder; the rare earth hafnium salt pre-reacted powder is a RE-Hf-O composite oxide, and its theoretical density is between that of rare earth oxide powder and hafnium oxide powder; the hafnium oxide powder includes micron-sized and nano-sized particles; S2. After adding the ceramic slurry to the initiator, inject it into the mold and centrifuge the mold around its own axis to obtain a gradient slurry preform. The centrifugation process includes at least two stages, with a centrifugation acceleration of no more than 1200 g and a centrifugation time of no more than 15 min in any stage. The last stage also includes initiating gelation. S3. The gradient slurry preform is gelled and solidified to obtain a wet preform; S4. The wet blank is dried, degreased and pre-sintered to obtain a pre-sintered blank with a radial composition gradient; S5. The pre-sintered blank is sintered to obtain a centrifugal self-stratified neutron absorbing material, wherein the difference in the Hf / (Hf+RE) molar ratio between the outer surface and the center exceeds 0.15, and the change in the Hf / (Hf+RE) molar ratio along the radial direction does not exceed 0.05 / 100μm.
2. The preparation method according to claim 1, characterized in that: The rare earth hafnium salt pre-reacted powder is prepared by the following method: rare earth oxide powder and hafnium oxide powder are mixed at a RE2O3:HfO2 molar ratio of 1:1.5 to 1:2.5, ball-milled, and then kept at 1000 to 1500℃ for 1 to 8 h; the D50 particle size of the rare earth hafnium salt pre-reacted powder is 0.3 to 3 μm.
3. The preparation method according to claim 1, characterized in that: The D50 particle size of the micron-sized hafnium oxide powder is 0.5–10 μm, and the D50 particle size of the nano-sized hafnium oxide powder is 20–300 nm, and the mass ratio of the micron-sized hafnium oxide powder to the nano-sized hafnium oxide powder is 90:10–70:
30.
4. The preparation method according to claim 1, characterized in that: The theoretical density difference between the rare earth oxide powder and the hafnium oxide powder is not less than 1.5 g / cm³. 3 .
5. The preparation method according to claim 1, characterized in that: The solid volume fraction of the ceramic slurry is 45% to 60%; based on the total molar amount of solid phase, the rare earth oxide powder accounts for 5% to 45%, the hafnium oxide powder accounts for 40% to 90%, and the rare earth hafnium salt pre-reacted powder accounts for 3% to 40%.
6. The preparation method according to claim 1, characterized in that: The centrifugation process includes three sequential stages; wherein, In the first stage, centrifuge at a centrifugal acceleration of 50 g to 300 g for 0.5 to 5 min; In the second stage, centrifuge at a centrifugal acceleration of 300 g to 1200 g for 1 to 15 minutes; In the third stage, centrifugation was carried out at a centrifugal acceleration of 50 g to 300 g for 0.5 to 10 min, which simultaneously induced gelation.
7. The preparation method according to claim 1, characterized in that: The aqueous colloidal solution contains an organic monomer and a crosslinking agent, wherein the organic monomer is acrylamide, the crosslinking agent is N,N'-methylenebisacrylamide, and the initiator is ammonium persulfate; the gelation initiation is initiated by heating.
8. The preparation method according to claim 1, characterized in that: In step S4, before the pre-sintering, the wet blank or the dried blank is subjected to cold isostatic pressing treatment at a pressure of 100-300 MPa and a holding time of 5-20 min.
9. The preparation method according to claim 1, characterized in that: In step S4, the pre-sintering temperature is 800–1250°C and the holding time is 1–10 h; in step S5, the sintering temperature is 1300–1700°C.
10. A centrifugally self-stratifying neutron absorbing material, characterized in that: The centrifugal self-stratified neutron absorber material is prepared by the preparation method according to any one of claims 1 to 9; the centrifugal self-stratified neutron absorber material comprises, from the inside out, an absorber core rich in rare earth oxides, a transition region containing rare earth hafnium salts, and a corrosion-resistant outer shell rich in hafnium oxide.
11. The application of the centrifugally self-stratified neutron absorbing material of claim 10 in a control rod core.